Using a theoretical approach to identify factors influencing adherence to an exercise programme for adults with venous leg ulcers. (April 2018) - O'Brien, Jane; Finlayson, Kathleen; Kerr, Graham; Shortridge-Baggett, Lillie; Edwards, Helen
This study assessed the relationships between self-efficacy, outcome expectations, fear-avoidance beliefs and adherence to an exercise for a home-based exercise programme for adults with venous leg ulcers. Patients ( n =63) were randomised to receive either an intervention or usual care group. Of those in the exercise intervention group, 59per cent adhered to the exercise protocol more than 75per cent of the time. There was a significant relationship between self-efficacy and outcome expectations, and both of these constructs were significantly related to adherence to the leg exercise programme. Adherence significantly correlated with wound healing indicating a possible pathway to healing.